Bacterial decomposition of allochthonous organic matter in shallow subtropical lakes. Issue 4 (1st December 2021) - Gayer, Pâmela R.; Guimarães, Pablo S.; Albertoni, Edélti F.; Hepp, Luiz U.
Abstract: Shallow lakes favour the development of aquatic macrophytes that can influence the limnological characteristics of these environments. In addition to macrophytes, allochthonous organic matter contributes to the metabolism of lakes through the bed of decomposing detritus. Among the decomposing microorganisms, bacteria can be important in the processing of organic matter when the abundance of fungi and invertebrates is low. The present study evaluated the effects of macrophyte coverage on bacterial‐mediated leaf decomposition of allochthonous debris in shallow subtropical lakes. Litter bags were incubated with senescent leaves of Erythrina crista ‐ galli in six shallow lakes, three with high (HML) and three with low (LML) macrophyte coverage. After 2, 7, 15 and 35 days of incubation, a set of litter bags was removed from each lake for bacterial, environmental and mass‐loss analyses. Decomposition rates were higher in the LML (49% of remaining mass), compared to the HML (63% of remaining mass). The bacterial density and biomass were higher in the LML. Limnological variables influenced bacterial morphotypes, especially branched filament. Thus, the high coverage of aquatic macrophytes can be a main factor influencing the bacterial colonization in the debris, delaying the decomposition process in these ecosystems.